2023
DOI: 10.2147/opth.s399989
|View full text |Cite
|
Sign up to set email alerts
|

Delphi Panel Consensus Regarding Current Clinical Practice Management Options for Demodex blepharitis

Abstract: To obtain consensus on Demodex blepharitis (DB) treatment using a modified Delphi panel process. Methods: Literature search identified gaps in knowledge surrounding treatment of DB. Twelve ocular surface disease experts comprised the Demodex Expert Panel on Treatment and Eyelid Health (DEPTH). They completed a live roundtable discussion in addition to 3 surveys consisting of scaled, open-ended, true/false, and multiple-choice questions pertaining to the treatment of DB. Consensus for scaled questions using a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…While ocular itching is the most common symptom of Demodex blepharitis, it can also present with a range of other symptoms like dryness, discharge, eye redness, burning, tearing, foreign body sensation, pain and blurred vision [ 2 ]. The pathognomonic clinical sign of Demodex infestation is the presence of collarettes, which are cylindrical dandruff debris structures that extrude out of the base of the eyelashes and consist of mite waste products and eggs [ 3 ]. The main objective in treating Demodex blepharitis is to eliminate or significantly reduce the presence of collarettes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While ocular itching is the most common symptom of Demodex blepharitis, it can also present with a range of other symptoms like dryness, discharge, eye redness, burning, tearing, foreign body sensation, pain and blurred vision [ 2 ]. The pathognomonic clinical sign of Demodex infestation is the presence of collarettes, which are cylindrical dandruff debris structures that extrude out of the base of the eyelashes and consist of mite waste products and eggs [ 3 ]. The main objective in treating Demodex blepharitis is to eliminate or significantly reduce the presence of collarettes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathognomonic clinical sign of Demodex infestation is the presence of collarettes, which are cylindrical dandruff debris structures that extrude out of the base of the eyelashes and consist of mite waste products and eggs [ 3 ]. The main objective in treating Demodex blepharitis is to eliminate or significantly reduce the presence of collarettes [ 3 ]. This condition was typically managed with over-the-counter remedies mainly consisting of products based on tea tree oil that are irritating and are toxic to the meibomian glands, with treatment often ineffective [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,17 Recently, an expert panel concluded that patients with more than 10 collarettes should be treated, irrespective of symptoms, with reductions in collarettes used to evaluate treatment efficacy. 77 A few studies have used collarette or CD scoring or classification systems to evaluate treatment efficacy. Karakurt et al, 67 for example, graded CD qualitatively as none (0), light (1), moderate (2), or severe (3).…”
Section: Measures Of Efficacymentioning
confidence: 99%
“… 29 , 76 An effective treatment for Demodex blepharitis would likely decrease the need for mechanical intervention such as MBE or lid scrubs. 77 …”
Section: Disease Managementmentioning
confidence: 99%